2020
DOI: 10.3390/atmos11030236
|View full text |Cite
|
Sign up to set email alerts
|

A Review and Insights for Eleven Years of Urban Microclimate Research Towards a New Egyptian ERA of Low Carbon, Comfortable and Energy-Efficient Housing Typologies

Abstract: Since the mid-1970s, urban development in Egypt has sprawled far from the distinguished compact arid built environment, as the court-yarded housing typologies that completed the vernacular picture of desert architecture have been discarded in the early 20th century. This has motivated urban microclimate research in Egypt. The main objective was initially to improve outdoor thermal comfort. Therefore, Egyptian research started with assessing different existing patterns for the sake of climate responsive and sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 87 publications
2
13
0
Order By: Relevance
“…The results showed good agreement between measured parameters and ENVI-met simulation outputs, regarding air temperature and humidity, as with [32,37]; however, the insignificant calculation of the wind speed parameter was considered unreliable. This finding is similar to that of Elwy et al [19], and could be attributed to the non-windy site conditions and the atypical extreme heatwave on the measuring day. Therefore, we used 24 h forced entry into the ENVI-met boundary conditions from the output exported from Meteonorm.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results showed good agreement between measured parameters and ENVI-met simulation outputs, regarding air temperature and humidity, as with [32,37]; however, the insignificant calculation of the wind speed parameter was considered unreliable. This finding is similar to that of Elwy et al [19], and could be attributed to the non-windy site conditions and the atypical extreme heatwave on the measuring day. Therefore, we used 24 h forced entry into the ENVI-met boundary conditions from the output exported from Meteonorm.…”
Section: Discussionsupporting
confidence: 91%
“…Contrast is added when distinct colors are present in a space. Trees have other benefits; for example, they replace carbon gas emissions with oxygen, purify the air, shield from noise, and provide security and privacy, especially in private and semi-public spaces [19]. They also increase the land value with respect to the real-estate market [20].…”
Section: Urban Treesmentioning
confidence: 99%
“…In many research studies, ENVI-met has proven its success in performing thermal simulations for outdoor areas. (M. Fahmy, Mahmoud, Elwy, & Mahmoud, 2020;Gehl Jan, 1996;Yang et al, 2011;Yilmaz, Mutlu, & Yilmaz, 2018;Nasrollahi, Ghosouri, Khodakarami, & Taleghani, 2020).These studies confirmed an agreement between the measured data (from the field measurements or observed data at the local meteorological stations) and simulated air temperatures. Envi-met has the capability to simulate the microclimate of any location all over the world.…”
Section: Envi-met Validation and Limaitationsupporting
confidence: 73%
“…Additionally, they pointed out that the applications of solar energy (e.g., photovoltaics (PV) and solar thermal (ST)) can be perfectly integrated with the building envelope components of heritage buildings [10,31]. Other similar studies were carried out in non-heritage buildings in Egypt, in a hot, dry climate, such as the work of Attia et al (2013) and Fahmy et al (2020) [20,32,33]. Fahmy et al focused only on analyzing existing studies concerned with urban microclimate and housing typologies and did not tackle specific strategies of the (RES) application in the Egyptian climate.…”
Section: Literature Reviewmentioning
confidence: 99%